Low Humidity Characteristics of Polymer-Based Capacitive Humidity Sensors - Majewski Jacek (Metrology and Measurement Systems, 2017)
Polymer-based capacitive humidity sensors emerged around 40 years ago; nevertheless, they currently constitute large part of sensors’ market within a range of medium (climatic and industrial) humidity 20−80%RH due to their linearity, stability and cost-effectiveness. However, for low humidity values (0−20%RH) that type of sensor exhibits increasingly nonlinear characteristics with decreasing of humidity values. This paper presents the results of some experimental trials of CMOS polymer-based capacitive humidity sensors, as well as of modelling the behaviour of that type of sensor. A logarithmic functional relationship between the relative humidity and the change of sensor output value at low humidity is suggested.